Russian Constructivism and Suprematism 1914-1930. (London : Annely Juda Fine Art, 1991)
Chashnik, Ilya ; Ermilov, Vassily ; Exter, Alexandra ; Gabo, Naum ; Kliun, Ivan ; Lissitzky, El ; Malevich, Kasimir ; Mansurov, Pavel ; Matiushin, Mikhail ; Popova, Liubov ; Rodchenko, Alexander ; Rozanova, Olga ; Senkin, Sergei ; Suetin, Nikolay ; Tatlin, Vladimir
biog. per kunstenaar
Engels
Russian Constructivism and Suprematism 1914-1930, Annely Juda Fine Art, London, 27 June - 14 September 1991
boek
Keywords: Rusland